The Feasibility of Virtual Service-Learning - Lorie Cook-Benjamin; Chapman Rackaway Ft. Hays State University (The Advocate, 2015)
This study assessed attitudes regarding the effectiveness of disciplinebased service-learning within the virtual environment. The study, conducted at a comprehensive Midwestern state university, collected data using a Likert-scale survey and reflections. Research on virtual service-learning is sparse making it a field ripe with research opportunities. The quantitative results suggest virtual learners are not provided opportunities for service-learning commensurate with their in-person cohort. For one discipline, the qualitative data suggests there is a need for multiple and synchronous communication, and reflection at multiple points throughout the semester. The study validated literature on the need to use active learning pedagogies across disciplines.